Thermoresponsive and Injectable Hydrogel for Tissue Agnostic Regeneration (Adv. Healthcare Mater. 23/2022). Issue 23 (8th December 2022) - Calder, Dax; Fathi, Ali; Oveissi, Farshad; Maleknia, Simin; Abrams, Terence; Wang, Yiwei; Maitz, Joanneke; Tsai, Kevin Hung‐Yueh; Maitz, Peter; Chrzanowski, Wojtek; Canoy, Ivan; Menon, Vivek Ashoka; et al.
Abstract : Injectable Hydrogels The coil structure represents the synthetic chemical composition of the featured biomaterial. The fluid network is temperature responsive and transitions into an adhesive hydrogel matrix upon administration. The resulting scaffold moulds within any defect and provides a regenerative network for cell in growth and subsequent tissue regeneration. The work represented here can be found in article 2201714 by Ali Fathi, Fariba Dehghani, and co‐workers.